Membrane chemical reactor for biodiesel esterification - Chan, Benjamin Jia Jun. (2009)
Abstract Biodiesel is a clean burning fuel made from organic sources such as vegetable oils and animal fats. Biodiesel is chemically composed of Fatty Acid Alkyl Esters (FAME). It is produced via the transesterification reaction, which converts triglycerides (TG) found in the feedstock oils to FAME. This study seeks to incorporate the use of a Membrane reactor in the production of Biodiesel. The immiscibility of oil and methanol forms the basis of the principle of membrane reactor operation. A membrane reactor prototype was put together, using a microfiltration ceramic membrane. FAME was produced via the base-catalyzed transesterification reaction in the membrane reactor system. 2 runs were conducted, one with the membrane reactor as a filtration device, and the other in cross flow mode. The reaction was conducted at 40°C. The flow rates, trans-membrane pressure were recorded and the membrane flux calculated. The permeate stream was collected at fixed time intervals and sent for testing by Gas Chromatography (GC). The GC tests shows the composition of the permeate stream, and the completeness of the transesterification reaction at different times. The results of this research showed that the ceramic membrane was a suitable candidate for its chemical inertness, but the pore size of the membrane used here was too big. Glycerol was successfully removed from the FAME produced, which aids the purification of the biodiesel produced via the transesterification reaction.